Studi In Silico dan Prediksi Efisiensi Administrasi In Vivo Senyawa Berpotensi Obat pada Tumbuhan Cempedak (Artocarpus integer) - Gusti Nur Aida Fasha (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Artocarpus integer (cempedak) is a tropical plant widely used in South Kalimantan, known for its rich bioactive compounds, which make it a promising source for drug discovery through in silico approaches. This study aims to identify and predict the potential of bioactive compounds from A. integer as drug candidates through an in silico approach. The data were obtained from the KNApSAcK database and analyzed using the SwissADME, SwissTargetPrediction, PASS Online, and GUSAR platforms to evaluate pharmacokinetic suitability, biological targets, pharmacological activities, and predictive toxicity. Four compounds were identified, namely Integrin, Oxyisocyclointegrin, Cyclointegrin, and Artoindonesianin F. The analysis revealed that the first three compounds comply with Lipinski's Rule of Five, indicating favorable metabolic properties. In contrast, Artoindonesianin F does not meet these criteria due to its high lipophilicity. Molecular target prediction suggested that the active compounds interact with enzyme groups such as proteases, kinases, and phosphodiesterases, which play crucial roles in the therapeutic mechanisms of various degenerative diseases and cancers. Based on PASS Online analysis, Oxyisocyclointegrin and Cyclointegrin exhibited high probabilities of biological activity (Pa > 0.9), including cell membrane stabilization, enhancement of TP53 gene expression, and inhibition of cytochrome P450 enzymes. Toxicity analysis using GUSAR indicated that both compounds possess low toxicity levels, with oral LD₅₀ values of 1437 mg/kg and 1164 mg/kg, respectively. Therefore, Oxyisocyclointegrin and Cyclointegrin show promising potential as natural bioactive compound candidates for further development in natural product-based pharmacotherapy research.